The Efficient and Effective Use of Exfoliative Urinary Markers. Issue 3 (May 2016) - Whitson, Jared M.; Porten, Sima P.; Hussein, Ahmed A.; Meng, Maxwell V.
Abstract : Introduction: : Multiple exfoliative urinary markers are available and commonly used in various clinical settings. However despite an abundance of primary data and reviews an evidence‐based application in the detection and monitoring of bladder cancer is lacking. We provide a framework in which the clinician caring for patients at risk for and diagnosed with bladder cancer can easily understand and incorporate these tools into routine practice. Methods: : We reviewed the English language literature regarding voided urinary markers for bladder cancer, focusing on prior systematic reviews published since 2003. Available data on sensitivity and specificity were analyzed in the context of 3 scenarios of application, including screening for bladder cancer, evaluating patients with hematuria and monitoring disease after a bladder cancer diagnosis. We defined and applied the relevant statistical tools, and provide rational recommendations for clinical application. We also summarized issues of cost‐effective utilization of these tests. Results: : Consistent with existing opinions there is no current role for any urinary marker in screening for bladder cancer. This is the result of low disease prevalence even in purportedly high risk groups. In patients with microscopic hematuria a negative urinary biomarker may spare further evaluation with cystoscopy while regardless of the urinary marker result those with gross hematuria are at sufficient risk to justify cystoscopy. Patients with lower risk bladder urothelial carcinoma may require less frequent cystoscopy if urinary markers are negative. Patients at high risk are at low risk for undetected cancer if cystoscopy and voided marker are negative. Conclusions: : Available information on exfoliative urinary markers suggests a clear role in bladder cancer diagnosis and monitoring. We provide an evidence‐based practical approach to application in routine clinical practice. Our approach must be considered in the context of current practice guidelines. Additional studies are required to determine the most cost‐effective algorithms and novel markers that may further enhance the role of these biomarkers.